Halal Tourism and Conventional Tourism Contestation: An Analysis of the Dynamics of Muslim-Friendly Tourism in Lombok - Muharis Muharis; Muhammad Taufik; Baiq Nadia Nirwana; Fidiatunisa; Sirajudin (Soshum: Jurnal Sosial dan Humaniora, 2026)
This study examines the interaction between halal and conventional tourism in Lombok, which has emerged as a leading halal tourism destination in Indonesia. Using a mixed methods approach and sequential explanatory design, the study maps levels of compliance with and perceptions of Muslim-friendly tourism and analyses the dynamics of the interaction between the two paradigms. Findings indicate that although the majority of the tourism industry in Lombok has adopted halal tourism principles, their implementation remains variable, particularly in the micro and small business sector. Furthermore, tensions exist between global market needs and Sharia principles that may impact Lombok's image as a Muslim-friendly destination. This study proposes an integration model that emphasises flexibility in service delivery and market segmentation to achieve a balance between halal and conventional tourism, which is expected to strengthen Lombok's competitiveness as an inclusive global destination. These findings provide an important contribution to the development of more adaptive and relevant halal tourism in Indonesia and Southeast Asia.